De cirurgião a comerciante de couros: a trajetória do licenciado Sebastião Gomes de Carvalho, o primeiro cirurgião do Continente de São Pedro - Carvalho, Rogério Machado de (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation deals with the trajectory of the graduate Sebastião Gomes de Carvalho, the first surgeon of Continente de São Pedro, a name given to the current state of Rio Grande do Sul in the 18th century. To reconstruct his trajectory, we present information about the training and functions that a surgeon in the 18th century should perform and about his environment, the political context and living conditions of the population who lived - or who began to live after the official settlement initiatives - in the region for which he was assigned in 1736, a year before the foundation of the Jesus Maria José fortress. Considering that the surgeon inserted himself in the local elite, through his work in commerce and politics, we identified and discussed, from the methodological frameworks of the topics covered, the social ascension strategies employed by Gomes de Carvalho, an individual who was not noble and who exercised – as an initial occupation – a trade that had no prestige and was poorly paid. Therefore, we analysed documents that are in the Proceedings of the Historical Archive of Rio Grande do Sul, baptismal records, correspondence and reports of travellers, comparing them with the reference bibliography on the themes contemplated in the dissertation. The research is part of the studies of Social History, in the dialogue with the Medicine, Health and Diseases History, to the extent that we seek, through the work of surgeon Gomes de Carvalho, to also characterise the health conditions and the arts of healing practised in the first half of the 18th century on the Continente de São Pedro.
Keywords: Sebastião Gomes de Carvalho; Trajetória; Artes de curar; Continente de São Pedro; Século XVIII; Trajectory; Healing arts; 18th century; ACCNPQ::Ciências Humanas::História